The impact of energy structure on sectoral carbon emissions: Evidence from China - Lei Bei; Chaolong Duan; Yongkui Du; Chao Wu; Wentao Li; Hanping Mao; Wu Yang; Ben Wang; Linlin Xu; Ruisi Wang; Xiao Liu; Lushi Sun; et al. (Energy and Climate Change, 2026)

Strong dipole-dipole interaction-enhanced dual-network piezoelectric hydrogels for long-term pulse monitoring and machine learning-based object recognition - Zhentao Lu; Kai Xu; Xigen Huang; Weihao Li; Junchen Li; Li Li; Shuwu Liu; Hanping Xu; Changhao Li; Limin Lu; Rumin Fu (Chemical Engineering Journal, 2026)

Discrete element modeling of a cultivated soil-residual film composite and simulation of spatial excavation-throwing kinematics - Shilong Shen; Jiaxi Zhang; Hanping Mao; Yongxin Jiang; Yichao Wang; Xin Zhou; Xuanfeng Liu (Computers and Electronics in Agriculture, 2026)

Dynamic gamma correction-guided CNN for low-light corn tassel enhancement in intelligent detasselling systems - Qirui Wang; Yang Liu; Shenyao Hu; Yuting Yan; Bing Li; Hanping Mao (Computers and Electronics in Agriculture, 2026)

Design and experiment of a ridge-surface based cutting height active adjustment system for a leafy vegetable harvester - Haitao Peng; Zhiyu Zuo; Guoxin Ma; Luhua Han; Ze Liu; Hanping Mao (Biosystems Engineering, 2025)

Identification and expression analysis of olfactory genes from Ephestia elutella (Lepidoptera: Pyralidae) antennal transcriptome - Guiyao Wang; Yueliang Bai; Hanping Zhou; Yingjie Liu; Taibo Liang; Keke Sun; Yongsheng Wang; Qiang Xu; Jianwei Wang (Journal of Asia-Pacific Entomology, 2025)

A hybrid approach using chained-SVR, MODE and DEA to optimize environmental control values in plant factories - Miao Lu; Haoling Liu; Jinghua Xu; Huimin Li; Pan Gao; Hanping Mao; Jin Hu (Computers and Electronics in Agriculture, 2025)

A novel tin dioxide field effect transistor with PMMAA functionalized organic passivation layer for the detection of the cortisol in saliva - Caiyuan Liao; Rong Zou; Qixin Zhou; Huan-Yu Liu; Song-Mei Liu; Long Fang; Gang Chang; Hanping He (Chemical Engineering Journal, 2025)

Identify the impact of pyrolysis temperature on preparation of carbon nanotubes by catalytic reforming polypropylene - Ning Cai; Qingyu Liu; Xiaoqiang Li; Shujiang Li; Haiping Yang; Hanping Chen (Waste Management, 2024)

Insight into the mechanism of lignin amination pretreatment on lignin structure and its pyrolysis property for lignin valorization - Zihao Liu; Jiawen Zeng; Zhiguo Dong; Yingquan Chen; Haiping Yang; Hanping Chen (Chemical Engineering Journal, 2024)

Smart windows based on ultraviolet-B persistent luminescence phosphors for bacterial inhibition and food preservation - Xiaohui Lin; Chonghui Li; Shicai Xu; Jihua Wang; Huanxin Yang; Yikai Qu; Qingshuai Chen; Zhenghua Li; Mengyu Su; Guofeng Liu; Hanping Liu; Jilei Yang; et al. (Food Chemistry, 2024)

The role of exogenous hydrogen sulfide in mitigating cadmium toxicity in plants: A comprehensive meta-analysis - Hanping Cao; Kejin Song; Yingying Hu; Qingxiao Li; Tengfei Ma; Rui Li; Nan Chen; Shunqin Zhu; Wanhong Liu (Environmental Science and Pollution Research, 2024)

Association of systemic inflammation with the obesity paradox in cancer: results from multi-cohort studies - Hailun Xie; Lishuang Wei; Heyang Zhang; Guotian Ruan; Xiaoyue Liu; Shiqi Lin; Jinyu Shi; Chenan Liu; Xin Zheng; Yue Chen; Hanping Shi (Inflammation Research, 2024)

Calibration and measurement of micrometre-scale pollen particles for discrete element method parameters based on the Johnson-Kendal-Roberts model - Qiang Shi; Bin Wang; Hanping Mao; Yong Liu (Biosystems Engineering, 2024)

Effects of EDTA and Organic Acids on Physiological Processes, Gene Expression Levels, and Cadmium Accumulation in Solanum nigrum Under Cadmium Stress - Wanhong Liu; Ting Yu; Hanping Cao; Xiang Peng; Ya Yang; Rui Li (Journal of Soil Science and Plant Nutrition, 2023)

Performance, comparison and utilization of reduced sulfur (−2) compounds (S2−, FeS and SCN−) in autotrophic denitrification process by thiosulfate-driven autotrophic denitrifier - Liangliang Liu; Yangjin Xu; Hanping Pan; Cunxue Yu; Qian Liu; Chaohai Wei; XiuFang Zhao; Meirong Su; Jianxin Pan (Environmental Research, 2023)

Thermal behavior and kinetic mechanism of microalgae and model compounds - Tang Ziyue; Wei Chen; Xu Chen; Mingwei Xia; Yingquan Chen; Haiping Yang; Hanping Chen; Liu Xiaorui (Fuel, 2023)

The efficient utilization of thiocyanate on simultaneous removal of ammonium and nitrate through thiosulfate-driven autotrophic denitrifiers and anammox - Liangliang Liu; Yangjin Xu; Cunxue Yu; Hanping Pan; Chaohai Wei; XiuFang Zhao; Meirong Su; Jianxin Pan (Bioresource Technology, 2023)

Valorization of the microalgae fixing CO2 from flue gas by co-hydrothermal liquefaction with high-protein microalgae: Denitrogenation of bio-oil by ash and high energy recovery - Huihui Liu; Youjian Zhu; Wei Yang; Yawei Li; Haiping Yang; Yingquan Chen; Xianhua Wang; Hanping Chen (Fuel, 2023)

Ensemble learning system to identify nutritional risk and malnutrition in cancer patients without weight loss information - Liangyu Yin; Jie Liu; Ming Liu; Jin Zheng; Aiguo Xu; Quanjun Lyu; Yongdong Feng; Zengqing Guo; Hu Ma; Jipeng Li; Zhikang Chen; Hui Wang; et al. (Science China Life Sciences, 2023)

Mechanism study on pyrolysis interaction between cellulose, hemicellulose, and lignin based on photoionization time-of-flight mass spectrometer (PI-TOF-MS) analysis - Peixuan Xue; Ming Liu; Haiping Yang; Han Zhang; Yingquan Chen; Qiang Hu; Shihong Zhang; Hanping Chen (Fuel, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Designing a Multi-Parameter Method to Assess the Adaptation Period of Crucian Carp under Stress Conditions of the Bionic Robot Fish - Bin Wang; Hanping Mao; Jian Zhao; Yong Liu; Yafei Wang; Xiaoxue Du (Fishes, 2022)
Changes in the physiological and behavioral states of fish are affected by foreign substances. Therefore, fish need a certain adaptation period to eliminate the stress response. Herein, in order to determine the adaptation period, the bionic robot fish was used to obtain behavioral information about crucian carp, which was tested at five time points (1st, 7th, 14th, 21st and 28th day) within 28 days. First, the fear response and exploratory behavior of crucian carp affected by three-color bionic robot fish were explored. Then, according to the measurement results of the behavior, morphology, and feeding, and the physiological and biochemical properties of the crucian carp, a multi-parameter evaluation method was proposed to determine the adaptation period of the crucian carp under this monitoring mode. The results showed that more than 4 areas were occupied by crucian carp from the 21st day. From the 16th day, the number of crucian carp swimming with clear outlines gradually increased. The number of abnormal swimming occurrences decreased on day 13. More than 80% of the crucian carp body color returned to dark on the 23rd day. The crucian carp did not respond to food until day 19, when most of the crucian carp began to scramble for food. Food consumption reached more than two thirds on day 22. In addition, glucose and total protein leveled off after day 21, when mean hemoglobin levels were highest. Triglycerides showed a trend of first decreasing and then increasing. The pigmented area of the skin section gradually decreases and eventually stabilizes. In summary, it takes at least 23 days for the crucian carp to adapt to the influence of the bionic robot fish.

The combination of metabolic syndrome and inflammation increased the risk of colorectal cancer - Tong Liu; Yali Fan; Qingsong Zhang; Yiming Wang; Nan Yao; Mengmeng Song; Qi Zhang; Liying Cao; Chunhua Song; Hanping Shi (Inflammation Research, 2022)
Background Inflammation and metabolic syndrome (MetS) may act synergistically and possibly accelerate the initiation and progression of colorectal cancer (CRC). We prospectively examined the joint effect of MetS and inflammation on the risk of CRC. Methods We studied 92,770 individuals from the Kailuan study. MetS was defined based on the presence of three or more of the following components. (1) high glucose: FPG > 5.6 mmol/L; (2) high blood pressure: SBP ≥ 130 mmHg or DBP ≥ 85 mmHg; (3) high triglycerides: triglycerides > 1.69 mmol/L; (4) low HDL-C: HDL-C < 1.04 mmol/L in men or 1.29 mmol/L in women; and (5) visceral adiposity: waist circumference ≥ 85 cm in men or 80 cm in women. Inflammation was defined as hs-CRP ≥ 3 mg/L. We divided participants into four groups for the primary exposure according to the presence/absence of inflammation and presence/absence of MetS. Cox proportional hazards regression models were used to evaluate the association of MetS and/or inflammation with the risk of CRC. Results Compared with metabolically healthy noninflammatory individuals, inflammatory participants without MetS and inflammatory participants with MetS were associated with a 1.3-fold and 4.18-fold increased risk of CRC with corresponding HRs (95% CI) of 1.34 (1.09, 1.64) and 4.18 (3.11, 5.62), respectively. The combination of MetS and inflammation was associated with the highest risk of CRC in all subgroups, especially among participants who were female, in younger age, and obese. Sensitivity analyses further validated our primary findings. Conclusions We found the combination of MetS and inflammation could significantly increase the risk of CRC. Including CRP in the diagnosis of MetS may help to identify additional high-risk participants who should be targeted for early diagnosis and prevention of CRC. Trial registration Kailuan study, ChiCTR–TNRC–11001489. Registered 24 August, 2011-Retrospectively registered, http:// www.chictr.org.cn/showprojen.aspx?proj=8050

Effects of Different Temperatures on the Antibacterial, Immune and Growth Performance of Crucian Carp Epidermal Mucus - Bin Wang; Guoxin Ma; Yong Liu; Yafei Wang; Xiaoxue Du; Qiang Shi; Hanping Mao (Fishes, 2021)
Fish is one of the important sources of energy and protein, and proper water temperature is key to successful fish breeding. The authors of this study evaluated crucian carp growth, mucus antibacterial properties, and immune indicators at 17, 21, 24, 27, and 31 °C. The results indicated that in the range of 17–31 °C, the resistance of epidermal mucus to Vibrio harveyi decreased with temperature rising. At 24 and 27 °C, the activities of lysozyme and catalase significantly increased; alkaline phosphatase activity, superoxide dismutase activity, and total protein concentration first increased and then decreased with rising temperature; the highest values were observed at 24 °C, with increases of 56.55%, 26.64%, and 44.52%, respectively, compared to those under the 17 °C treatment. When the treatment reached 27 °C, the temperature had an effect on the growth and antibacterial properties of crucian carp, and the activities of alkaline phosphatase and superoxide dismutase were significantly reduced. At temperatures of 17–24 °C, the survival rate of crucian carp could reach more than 93%, and at the temperature of 24 °C, the specific growth rate reached the highest value of 43.29%. Therefore, the most favorable temperature for the long-term breeding of crucian carp was found to be 24 °C. This study provides a favorable experimental basis for the establishment of intelligent aquaculture systems and the setting of water environment parameters.

Correlations between 13 Trace Elements and Circulating Tumor Cells in Patients with Colorectal Cancer in Guangzhou, China - Hetao Wang; Hao Liu; Meijuan Zhou; Hanping Shi; Mei Shen (Biological Trace Element Research, 2020)

High prevalence and viremia of human pegivirus 2 in the HIV-infected population in Honghe Prefecture, Yunnan Province - Tianyi Li; Shixing Tang; Yingying Su; Zuoyi Bao; Xiaolin Wang; Yongjian Liu; Hanping Li; Jingwan Han; Zhichao Pei; Zhengwei Wan; Hang Fan; Yigang Tong; et al. (Archives of Virology, 2020)

Transient receptor potential vanilloid-3 (TRPV3) activation plays a central role in cardiac fibrosis induced by pressure overload in rats via TGF-β1 pathway - Yan Liu; Hanping Qi; Mingyao E; Pilong Shi; Qianhui Zhang; Shuzhi Li; Ye Wang; Yonggang Cao; Yunping Chen; Lina Ba; Jingquan Gao; Wei Huang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

An HBT-Based Near-Infrared Fluorescent Probe for Colorimetric and Ratiometric Detection of Bisulfite and its Application in Living Cells - Yuanchao Sun; Zhen Chen; Fengzao Chen; Heng Liu; Hanping He; Xiuhua Zhang; Shengfu Wang (Journal of Fluorescence, 2017)

Responses of soil microbial and nematode communities to aluminum toxicity in vegetated oil-shale-waste lands - Yuanhu Shao; Weixin Zhang; Zhanfeng Liu; Yuxin Sun; Dima Chen; Jianping Wu; Lixia Zhou; Hanping Xia; Deborah A. Neher; Shenglei Fu (Ecotoxicology, 2012)